Adalimumab vs Infliximab in Pediatric Patients With Crohn's Disease: A Propensity Score Analysis and Predictors of Treatment Escalation - Bronsky, Jiri; Copova, Ivana; Kazeka, Denis; Lerchova, Tereza; Mitrova, Katarina; Pospisilova, Kristyna; Sulovcova, Miroslava; Zarubova, Kristyna; Hradsky, Ondrej (Clinical and translational gastroenterology, 2022)
INTRODUCTION: Two antitumor necrosis factor therapies (infliximab [IFX] and adalimumab [ADA]) have been approved for the treatment of pediatric Crohn's disease (CD) but have not been compared in head-to-head trials. The aim of this study was to compare the efficacy and safety of ADA and IFX by propensity score matching in a prospective cohort of pediatric patients with luminal CD and at least a 24-month follow-up. METHODS: Among 100 patients, 75 met the inclusion criteria, and 62 were matched by propensity score. We evaluated time to treatment escalation as the primary outcome and primary nonresponse, predictors of treatment escalation and relapse, serious adverse events, pharmacokinetics, and effect of concomitant immunomodulators as secondary outcomes. RESULTS: There was no difference between ADA and IFX in time to treatment escalation (HR = 0.63 [95% CI 0.31-1.28] P = 0.20), primary nonresponse (P = 0.95), or serious adverse events. The median (interquartile range) trough levels at the primary outcome were 14.05 (10.88-15.40) and 6.15 (2.08-6.58) µg/mL in the ADA and IFX groups, respectively. On a multivariate analysis, the combination of anti-Saccharomyces cerevisiae antibody negativity and antineutrophil cytoplasmic antibody positivity was a strong independent predictor of treatment escalation (HR 5.19, [95% CI 2.41-11.18], P < 0.0001). The simple endoscopic score for CD, L3 disease phenotype, and use of concomitant immunomodulators for at least the first 6 months revealed a trend toward significance on a univariate analysis. DISCUSSION: Propensity score matching did not reveal substantial differences in efficacy or safety between ADA and IFX. The anti-S. cerevisiae antibody negativity and antineutrophil cytoplasmic antibody positivity combination is a strong predictor of treatment escalation.
Keywords: Antibodies, Antineutrophil Cytoplasmic; lidé; výsledek terapie; Adalimumab; infliximab; Immunologic Factors; Crohnova nemoc; Prospective Studies; imunologické faktory; Infliximab; adalimumab; dítě; Child; Humans; prospektivní studie; protilátky proti cytoplazmě neutrofilů; Crohn Disease; tendenční skóre; Treatment Outcome; Propensity Score